Clinico-pathological characteristics among South African women with breast cancer receiving anti-retroviral therapy for HIV. (February 2019) - Phakathi, Boitumelo; Cubasch, Herbert; Nietz, Sarah; Dickens, Caroline; Dix-Peek, Therese; Joffe, Maureen; Neugut, Alfred I.; Jacobson, Judith; Duarte, Raquel; Ruff, Paul
Abstract: Purpose: Breast cancer is the most common cancer in women and a leading cause of cancer-related mortality worldwide. South Africa has the largest global burden of HIV infection and the largest anti-retroviral treatment (ART) program. This study aimed to analyse the association of HIV and ART use with breast cancer clinico-pathological characteristics. Methods: Study participants were females, newly diagnosed from May 2015 through September 2017 with invasive breast cancer at two academic Surgical Breast Units in Johannesburg, South Africa at the Charlotte Maxeke Johannesburg Academic Hospital and Chris Hani Baragwanath Academic Hospital. We compared HIV-positive and HIV negative patients' demographic and clinical-pathological characteristics at the time of breast cancer diagnosis. Results: Of 1050 patients enrolled, 1016 (96.8%) had known HIV status, with 226 (22.2%) being HIV positive. HIV positive patients were younger (median (IQR) age 45 (40–52) years), than HIV-negative patients (median (IQR) age 57 (46–67)) (p < 0.001). HIV positive patients were more likely to be diagnosed with late stage breast cancer (p = 0.01). However, HIV positive patients receiving ART at the time of breast cancer diagnosis were less likely to present with metastatic disease than those not on ART (p = 0.05). Conclusion: HIV-positive patients present with breast cancer at a younger age and later stage disease than HIV-negative patients. Neither the duration of HIV infection nor ART use was associated with clinico-pathological characteristics of breast cancer. Highlights: Fifty-five percent of patients presented with late stage disease (Stage III/IV). HIV positive patients with breast cancer presented at a younger age. HIV positive patients presented with late stage disease. Use of ART did not affect the clinicopathological characteristics of breast cancer. Duration of HIV infection did not affect the characteristics of breast cancer.